2014
DOI: 10.1371/journal.pgen.1004484
|View full text |Cite
|
Sign up to set email alerts
|

Common Transcriptional Mechanisms for Visual Photoreceptor Cell Differentiation among Pancrustaceans

Abstract: A hallmark of visual rhabdomeric photoreceptors is the expression of a rhabdomeric opsin and uniquely associated phototransduction molecules, which are incorporated into a specialized expanded apical membrane, the rhabdomere. Given the extensive utilization of rhabdomeric photoreceptors in the eyes of protostomes, here we address whether a common transcriptional mechanism exists for the differentiation of rhabdomeric photoreceptors. In Drosophila, the transcription factors Pph13 and Orthodenticle (Otd) direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 75 publications
3
48
0
Order By: Relevance
“…Our studies in Drosophila have now described a key regulatory link between rhabdomeric cell type patterning and differentiation mediated by Glass and Pph13. Both of these molecules are conserved in Pancrustaceans (Liu and Friedrich, 2004; Rivera et al, 2010) and homologs can be found in other protostomes including Apylsia californica ((Mahato et al, 2014) and NCBI Ref. Seq.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our studies in Drosophila have now described a key regulatory link between rhabdomeric cell type patterning and differentiation mediated by Glass and Pph13. Both of these molecules are conserved in Pancrustaceans (Liu and Friedrich, 2004; Rivera et al, 2010) and homologs can be found in other protostomes including Apylsia californica ((Mahato et al, 2014) and NCBI Ref. Seq.…”
Section: Resultsmentioning
confidence: 99%
“…As a first step in deciphering the potential evolutionary role of Glass, we investigated the function of Glass in Tribolium castaneum . Previous reports have demonstrated that both Glass and Pph13 are expressed in the developing photoreceptors of the Tribolium castaneum adult visual system (Liu and Friedrich, 2004; Mahato et al, 2014). Utilizing RNAi, SEM analysis of Glass RNAi knockdowns revealed an identical phenotype as compared to Drosophila ; there was an overall reduction of eye size, including a reduction in ommatidium number, as well as the presence of fused ommatidia (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rather than being brought about through targeted overexpression of master regulator genes, this induction results from the knockdown of the transcription factor orthodenticle (otd) (8). This phenotype is surprising: otd function has been studied in detail in Tribolium beetles, where it is needed for photoreceptor development in bilateral compound eyes but plays no detectable role in specifying the external morphology of eyes or the head in general (8,9), and in Drosophila, where it is required for proper rhabdomere and photoreceptor development in compound eyes (10) and for the formation of medial ocelli (11) (i.e., single-lens eyes that differ from compound eyes in many fundamental aspects). However, all extant scarabaeids and almost all other beetles, including Tribolium, lack medial ocelli (12), and even though dorsalization of compound eye compartments has evolved in a subset of insect taxa (the turbinate eyes of some male mayflies being an extreme example), completely distinct compound eyes developing middorsally on the cephalic vertex are not known from any extant insect lineages (13).…”
mentioning
confidence: 99%